2014
DOI: 10.1111/ijcp.12408
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the neutrophil-to-lymphocyte ratio in patients with acute-on-chronic liver failure

Abstract: The NLR measured at admission can serve as an independent predictor for 3-month mortality rate in AoCLF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 31 publications
1
32
0
8
Order By: Relevance
“…RDW was found to be an independent marker of short-term and long-term prognosis in intensive care units 10. NLR at admission served as an independent predictor of 3-month mortality rates in patients with acute-on-chronic liver failure 13. Increased pretreatment LMR was associated with a significantly more favourable prognosis in patients with solid tumours 12.…”
Section: Introductionmentioning
confidence: 96%
“…RDW was found to be an independent marker of short-term and long-term prognosis in intensive care units 10. NLR at admission served as an independent predictor of 3-month mortality rates in patients with acute-on-chronic liver failure 13. Increased pretreatment LMR was associated with a significantly more favourable prognosis in patients with solid tumours 12.…”
Section: Introductionmentioning
confidence: 96%
“…Recently several studies have found a high Neutrophil‐to‐Lymphocyte Ratio (NLR) to be indicative of a worse prognosis in a variety of different liver disease contexts: patients on the liver transplant waiting list, those with low MELD scores, hospitalised patients with cirrhosis, patients with acute‐on‐chronic liver failure (ACLF) and patients with decompensated liver disease without ACLF . The prognostic value of NLR in these studies appears additional to standard scores of liver function and to that of total white blood cell count (WCC) alone.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of an organism to reproduce cells becomes weaker with age and with some diseases [6,7], especially those with life-threatening pathologies [8,9]. The decrease in human life span (LS) with age is accompanied by a reduction in lymphocytopoietic activity in organisms, a marked decline in the production of naïve T cells, and an increase in granulocyte numbers [7,10]. As the mitotic phase of renewal in the lymphocytic compartment of PB is a valuable measure of current proliferative capacity, we considered that dividing mitotic activity of the lymphoid cells in PB by the number of circulating CD133 + HSCs (specific reproductive activity, sRA) might provide a more reliable measure of the long-term functional potential for lymphocytopoiesis.…”
Section: Strongly Proliferating Cd133mentioning
confidence: 99%